Finite-Time Stabilization of Networked Control Systems with Packet Dropout - Yanling Shang; Ye Yuan (Institute of Advanced Engineering and Science, 2014)
The problem of finite-time stabilization for networked control systems with both sensor-to-controller and controller-to-actuator packet dropouts is investigated in this paper.By using the iterative approach, the NCSs with bounded packet dropout is modeled as switched linear systems. Sufficient conditions for finite-time stabilization of the underlying systems are derived via linear matrix inequalities (LMIs). Lastly, an illustrative example is given to demonstrate the effectiveness of the proposed results.